GENDER DIFFERENCES AT THE WORKPLACE: SICKNESS ABSENCE AND PRODUCTIVITY LOSS AT WORK AND THEIR ASSOCIATION WITH HEALTH AND WORK-RELATED FACTORS - Djikanović, Bosiljka; Kouwenhoven-Pasmooij, Tessa A.; Kraaijenhagen, Roderik A.; Roeters van Lennep, Jeanine E.; Burdorf, Alex; Vasilev, Vladimir; Robroek, Suzan J.W. (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Differences in sickness absence and productivity loss at work between men and women are recognized but need to be better understood. Materials and methods: In a cross-sectional study, 10,407 employees from 37 companies in the Netherlands participated in a web-based health risk assessment, between 2010 and 2014. Self-reported short-term (<9 days) and long-term (10 or more days) sickness absences during the preceding 12 months were assessed. The questionnaire also asked about productivity loss at work, physical and psychosocial work-related factors, and health problems. Log-linear models were used to estimate prevalence ratios (PR), with 95% confidence intervals (CI). Results: Women, more often than men, experienced short-term and long-term sickness absence (PR 1.06, 95% CI 1.01 – 1.11, and PR 1.33, 95% CI 1.21 – 1.46, respectively) but were less likely to have productivity loss at work (more than 30%), (PR 0.90, 95% CI 0.81 – 0.99). In short-term sickness absence, gender differences were reduced by 20%, after controlling for psychosocial work-related factors, and by 60%, after controlling for health problems, separately. None of the factors mentioned above could explain a large productivity loss at work among men. Conclusions: Higher prevalence of sickness absence among women can partly be explained by psychosocial work-related factors and health problems. Further studies are needed to explore large productivity loss at work among men.